Early surgical management in pancreatic ascites on a background of chronic pancreatitis - Muthukumarasamy, Thiruvarul; Sachanandani, Kanchan Ashok; Harikrishnan, Sakhtivel; Satyanesan, Jeswanth (International Surgery Journal, 2020)
Background: Pancreatic ascites can occur as a complication of acute or chronic pancreatitis. In majority of cases, it is associated with pseudocyst or duct disruption. Management is initially conservative with paracentesis with nutritional support. Early surgery has been recently contemplated as primary management for pancreatic ascites. Methods: A prospective study was done over a duration of three years from November 2017 to October 2019 in patients of chronic pancreatitis presenting with pancreatic ascites. All patients underwent pancreatic protocol contrast enhanced computed tomography abdomen and magnetic resonance cholangiopancreatography, duct diameter and main pancreatic duct (MPD) disruption site. pseudocyst site was identified. After optimizing patients, early surgery was planned. Surgeries included either lateral pancreatic jejunostomy, if MPD were dilated. Pancreaticogastrostomy, cystogastrostomy or cystojejunostomy, if there was pseudocyst with extraneous impression over stomach or on mesocolon, and distal pancreatectomy (and/or) splenectomy. Results: Out of 20 cases of pancreatic ascites, 6 were of acute pancreatitis and conservatively managed and 14 were subjected to early primary surgery. 8 out of 14 patients underwent LPJ. 2/14 underwent pancreaticogastrostomy. 2/14 underwent cystogastrostomy and 1/14 underwent spleen preserving distal pancreatectomy. 1/14 underwent distal pancreatectomy and splenectomy. None of the patients had postoperative recurrence of pancreatic ascites. One patient developed Postoperative intra-abdominal collection which was drained. Mortality was 2/14 (14.2%), one died immediate postoperatively and another succumb to Pulmonary embolism on post-operative day-4. Pain scores were significantly reduced post-operatively. Conclusions: Primary early surgery directed towards primary pathology, as guided by MPD status, in selected patients with chronic pancreatitis with ascites leads to faster recovery of patient.